Channeling partitioning policies for multi-class traffic in LEO-MSS - Wang, Zhipeng; Mathiopoulos, P. Takis; Schober, Robert (IEEE Transactions on Aerospace and Electronic Systems, 2009)
This paper studies channel partitioning policies and channel resource prioritization techniques for handovers, which efficiently support multi-class traffic in low Earth orbit mobile satellite systems (LEO-MSS). Analytical methods are developed for evaluating the performance of complete partitioning (CP) and complete sharing (CS) with and without fixed channel reservation (FCR) for multi-class traffic in LEO-MSS. Furthermore, a novel threshold call admission (TCA) scheme which achieves better channel utilization and fair channel access is introduced and analyzed. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03